Silicon nitride engineering: role of hydrogen-bonding in Ge quantum dot formation. (11th September 2020) - Peng, Kan-Ping; Kuo, Yu-Hong; Chang, Li-Hsin; Hsiao, Chien-Nan; Chung, Tsai-Fu; George, Thomas; Lin, Horng-Chin; Li, Pei-Wen
Abstract: We report the lowering of the formation temperature of spherical-shaped Ge quantum dots (QDs) to 850 °C from our previously-reported 900 °C. This large reduction in QD formation temperature was achieved via the use of a hydrogenated, plasma-enhanced chemical-vapor deposited (PECVD) silicon nitride (SiN). The exquisite interplay between H, Ge, Si and O interstitials, controlling QD formation during the thermal oxidation of poly-SiGe layers deposited over PECVD-Six Ny : H, is further explored in order to understand the underlying mechanisms. We have experimentally observed that the high hydrogen content of the PECVD-Six Ny : H facilitates the lower-temperature (850 °C) oxidation of the nitride layer, while simultaneously being able to generate smaller diameter, fully coalesced Ge QDs within. Such heterostructures of SiN coupled-Ge QDs are a fundamental building block for the ultimate fabrication of active SiN-based Ge photonic devices.